Strategies for maintaining a handstand balance - Kerwin, D.; Trewartha, G. (Medicine & Science in Sports & Exercise, 2001)
The maintenance of balance is fundamental to all activities and requires a coordinated response by the CNS to afferent information. While the mechanisms of upright stance have been well studied, the strategies used by individuals to maintain inverted stance have been less well investigated. The altered nature of the movement context and the alternative demands it brings may highlight additional balance mechanisms. In this study a number of young male gymnasts performed handstand balances. Video and force data were synchronously recorded to allow two-dimensional inverse dynamics analysis of the movements to be conducted. Resultant joint torques were calculated from the combined video and force data by modelling the individual as a 4-segment system (hand, arms, trunk+head, and legs) with 3 joints (wrist, shoulder, hip). Centre of mass (CM) displacement was regressed against the three joint torques in a forward stepwise manner to determine which torques were primarily related to CM movement. The results of these regressions for a single trial from each of six subjects is shown in a graphic. The graphic shows that in general the calculated joint torques accounted for a substantial amount of the variance in CM displacement. In a number of trials the wrist torque was found to be the dominant predictor of CM movement and this was more evident in those subjects who had been given a higher rank in terms of steadiness of balance (independent of CM or torque values). Shoulder and hip torques accounted for more variance in CM movement in those subjects who had been assigned lower ranks.